Using Pollution Load Index (PLI) and Geoaccumulation Index (I-Geo) for the Assessment of Heavy Metals Pollution in Tigris River Sediment in Baghdad Region - Rabee, Adel Mashaan; Al-Fatlawy, Yaaroub Faleh; Abd own, Abd-Al-Husain Najim; Nameer, Mustafa (Al-Nahrain Journal of Science, 2011)
Six stations along Tigris river in Baghdad region were chosen to collect and assess the Mn, Ni, Pb, Cu and Cd contamination in sediments by using pollution load index (PLI) and geo-accumulation index (I-geo). Cd was found at the lowest concentration ranged between 0.3- 1.3 µg/g dry weight. Whereas, Mn was the highest ranging between 166 - 426 µg/g dry weight. Geo-accumulation index indicates that the sediment in the most of studied stations were slightly polluted (grade 1) with respect to Pb and Cd, while the sediments in all studied stations were unpolluted (grade 0) with respect to Mn, Cu and Ni. The values of Pollution Load Index (PLI) were found to be very low, and varied between 0.301-0.970, indicating that the studied stations in Tigris river were unpolluted by total of studied heavy metals.